A case report of rifampicin-induced dual adverse drug reaction: pancytopenia and hyperpigmentation - Barakath Ali, Thaslim Ridhwana; J., Lavina Mary; K., Pari; Khader, Fathima Juhaina M. Abdul (International Journal of Research in Medical Sciences, 2025)
Rifampicin is a first-line anti-tuberculosis (TB) drug widely used for its potent bactericidal activity. Although generally well tolerated, it can occasionally lead to uncommon adverse drug reactions (ADRs). Among these, pancytopenia and hyperpigmentation are extremely rare and may complicate therapy or cause unnecessary medication non-compliance. We report a case of a middle-aged female receiving anti-TB therapy (ATT) for past one week. She developed pancytopenia and brown patchy hyperpigmentation following rifampicin single regimen re-administration. Rifampicin was promptly withdrawn, and supportive management was provided. Progressive improvement in both hematological parameters and cutaneous pigmentation was observed after discontinuation. Rifampicin-induced pancytopenia results primarily from idiosyncratic or immune-mediated marrow suppression, whereas hyperpigmentation is believed to occur due to increased melanin production or dermal drug deposition. The visible change in the skin caused considerable distress and fear of continuing treatment, necessitating empathy and appropriate counseling to gain the individual’s trust. Health-care professionals should maintain a high index of suspicion for rare rifampicin-induced reactions presenting with simultaneous hematologic and dermatologic features. Early recognition, prompt drug withdrawal, and empathetic patient counseling are vital for favorable outcomes. Reporting even minor adverse effects contributes to pharmacovigilance and enhances awareness of such uncommon presentations.